Effectiveness Of Behavioral Cognitive Conselvation Using Self Monitoring Techniques Through Setting Lesson Study To Improve Self Order Class X Students Of Hospital Accommodation 2 Singaraja State 2 Vocational School - Agung Darma Putra; Ni Ketut Suarni; I Ketut Dharsana (Bisma The Journal of Counseling, 2019)
This study aims to determine the effectiveness of Behavioral Cognitive Counseling self monitoring techniques to improve the "self order" of class X Hospitality Accommodation 2 of SMK Negeri 2 Singaraja. This study uses a method of collecting data in the form of a self order questionnaire. The self order questionnaire has been tested for its validity and reliability. Based on the Independent Test Sample test, it was found that thit was 20,057 with df = (n1 + n2-2) = (35 + 36) - 2 = 69 with a significance level of 5%, and obtained a ttab = 1,667. Based on these results it can be concluded that the value of thit> ttab or 20,057> 1,667. The value of ES =4,761 then ES is in the high category. The results of this study indicate that cognitive behavioral counseling with self monitoring techniques through lesson study to improve Self Order of class X Hospitality Accommodation 2 of SMK Negeri 2 Singaraja.